2019
DOI: 10.18502/fid.v16i1.1111
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Self-Adhesive Flowable Composite, Conventional Flowable Composite and Resin-Modified Glass Ionomer Cement to Primary Dentin

Abstract: Objectives: This study aimed to compare the shear bond strength (SBS) of self-adhesive and conventional flowable composites and resin-modified glass-ionomer cement (RMGIC) to primary dentin. Materials and Methods: In this in vitro, experimental study, the buccal surface of 48 primary canine and first molar teeth was longitudinally sectioned to expose dentin. The teeth were randomly divided into three groups (n=16) of 37.5% phosphoric acid+ OptiBond+ Premise Flow composite (group 1), Vertise Flow composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 19 publications
0
26
2
7
Order By: Relevance
“…In total, 23 in vitro studies met inclusion criteria (published between 2012 and 2019) 8,9,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and most of them (n=18) used permanent teeth (ranging from 30 to 160) for the bonding tests. The bond strength of SAFRCs to primary teeth was evaluated in six studies, published between 2013 and 2019 16,22,26,30,34,38 . Vertise® Flow (Kerr Corp, Orange, CA, USA) (n=22) followed by Fusio™ Liquid Dentin (Pentron Clinical, Orange, CA, USA) (n=5) were the most tested SAFRCs, while Constic® was evaluated only in three studies 29,35,37 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 23 in vitro studies met inclusion criteria (published between 2012 and 2019) 8,9,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and most of them (n=18) used permanent teeth (ranging from 30 to 160) for the bonding tests. The bond strength of SAFRCs to primary teeth was evaluated in six studies, published between 2013 and 2019 16,22,26,30,34,38 . Vertise® Flow (Kerr Corp, Orange, CA, USA) (n=22) followed by Fusio™ Liquid Dentin (Pentron Clinical, Orange, CA, USA) (n=5) were the most tested SAFRCs, while Constic® was evaluated only in three studies 29,35,37 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The bond strength of SAFRCs was mainly assessed by shear bonding test (n=20) 8,16,[20][21][22][23][24][25][26][27][29][30][31][32][33][35][36][37][38][39] and tensile bonding test (n=3) 9,28,34 , using dentin (n=13), enamel (n=3) or both tissues (n=7) as substrates. Most studies tested the immediate bond strength of SAFRCs to enamel and dentin.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Almaz et al 16 measured the µSBS of self-adhering flowable composites to dentin samples, which was similar to the methodology adopted by Moslemi et al 11 The results showed that self-adhering flowable composites yielded the lowest µSBS, which was in agreement with our findings. Sachdeva et al, 19 Pacific et al, 20 and Poorzandpoush et al 21 used primary dentin samples for the assessment of shear bond strength. Their results were in line with ours, although we evaluated primary enamel.…”
Section: Discussionmentioning
confidence: 99%
“…The increased demand for cosmetics and tooth structure preservation leads to the development of adhesive restorative materials which bond to the enamel and dentin, where flowable composite resin is a type of adhesive restorative materials that gained popularity from its low viscosity, which lead to less tooth preparation in preventive resin restorations and superficial restorations 7,8 .…”
Section: Introductionmentioning
confidence: 99%